Fraternity in the Teaching of Pope Francis - Kućko, Wojciech (Collectanea Theologica, 2021)
The time of the coronavirus pandemic and the COVID-19 disease was an opportunity to ask anew many questions concerning interpersonal relations. In this context, Pope Francis tries to take up the therapy of fraternity in order to effectively and consistently contrast the “globalization of indifference” with the “globalization of fraternity and solidarity.” The aim of this article is to show the essence of fraternity in the teaching of Pope Francis (before the publication of papal encyclical letter Fratelli tutti about fraternity) in the context of the teaching of the Catholic Church. The article presents the biblical roots of fraternity as well as its inclinations in the Magisterium of the Second Vatican Council and subsequent popes. The reinterpretation of the term “fraternity” in Francis’ thought includes: the “mysticism of the fraternity,” its inter-religious and social character, its global fraternity on the level of bioethics and ecology, and its connection to the “theory of contradictions” (Germ.: Gegensatz), which the Pope took from R. Guardini.